Using Intake and Change in Multiple Psychosocial Measures to Predict Functional Status Outcomes in People With Lumbar Spine Syndromes: A Preliminary Analysis. - Hart, Dennis L.; Werneke, Mark W.; Deutscher, Daniel; George, Steven Z.; Stratford, Paul W.; Mioduski, Jerome E. (Physical Therapy, 2011)
Background. Managing patients with lumbar spine syndromes who are seeking outpatient physical therapy represents a complex problem where psychosocial constructs such as fear-avoidance beliefs regarding physical activities or work activities, somatization, and depressive symptoms may affect functional status (FS) outcomes. Objective. The purpose of this study was to determine whether intake or changes in fear-avoidance beliefs regarding physical or work activities, somatization, and depressive symptoms assessed simultaneously affect FS outcomes prediction. Design. This study was a secondary analysis of prospectively collected, longitudinal, observational cohort data. Methods. Data analyzed were from adult patients (n=323) with lumbar syndromes classified as elevated versus not elevated on single-item screening instruments for fear-avoidance beliefs regarding physical or work activities, somatization, and depressive symptoms at intake and discharge. Prediction of minimal clinically important difference in FS was assessed separately for intake and change from intake to discharge classifications using logistic regression models controlling for important variables. Results. Intake and change models were strong (McFadden rho-squared values = .31 and .49, respectively). Patients classified as not elevated in fear-avoidance beliefs regarding physical activities but elevated in fear-avoidance beliefs regarding work activities, somatization, and depressive symptoms at intake were 5 out of 100 times less likely to report clinically important outcomes compared with being elevated in each measure. Patients not elevated in fear-avoidance beliefs regarding work activities and somatization at intake and discharge were 8 to 14 times more likely to report clinically important outcomes compared with being elevated in each measure. Limitations. Sample size was limited. Data analyses were retrospective with no control of missing data. Conclusions. Combinations of multiple psychosocial constructs were important predictors of FS outcomes and may assist patient management by: (1) identifying patients with elevated psychosocial constructs at intake and (2) tracking change in psychosocial variables for improved outcomes prediction. This model may prove helpful for future clinical and research applications to determine optimal psychosocial screening methods.